Peran Pembangunan Parawisata Terhadap Peningkatan Kesejahteraan Masyarakat Pada Objek Wisata di Kabupaten Aceh Barat Daya - Vebrian Hasbullah; Yuliana Yuliana; Idal Bahri; Mawardi Mawardi; Yunida Pangastuti (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Tourism is currently experiencing rapid development in various developing countries such as Indonesia. Tourism is one sector that has potential to support regional development. The aim of this research is to look at the conditions of tourism in Southwest Aceh. As well as tourist attractions that influence the relationship between tourism and community income. Writing uses descriptive and qualitative methods to analyze data. To create systematic, factual paintings of events occurring at the present time, using population and samples, as well as primary data and questionnaires. The results of the research are: first, F-count is greater than f-table, namely 289,804 > 2.569031 and the value The calculated significance is 0.000 < 0.08 so, simultaneously there is an influence between tourism development (X1) and tourist attractions (X2) on community welfare (Y) at tourist attractions in Southwest Aceh. Second, the sig value is 0.000 < 0.08 and the t-value is 5.352 > 1.76279. shows a significant value, which means that there is an influence between tourism development (X1) on community welfare (Y) at tourist attractions in Southwest Aceh. Third, the sig value of 0.000 < 0.08 and the t-calculated value of 9.548 > 1.76279 shows a significant value, which means that there is an influence between the tourist attraction variable (X2) on community welfare (Y) at tourist attractions in Southwest Aceh. Fourth, the coefficient of determination test (R2) is 79.4%, the remaining 20.6% of community welfare (Y) at tourist attractions in Southwest Aceh is influenced by other variables that have not been examined in this research.